2014
DOI: 10.14309/crj.2014.32
|View full text |Cite
|
Sign up to set email alerts
|

Hematochezia Associated with Sevalamer-Induced Mucosal Injury

Abstract: We present a case of a 61-year-old woman with end-stage renal disease (ESRD) who developed painless hematochezia following initiation of anticoagulation. Work-up revealed a large ulceration in the sigmoid colon, and histologic images revealed sevelamer crystals embedded in the colonic mucosa, consistent with sevelamer crystal-mediated injury. This is a novel cause of gastrointestinal hemorrhage that has not previously been described in the literature. Physicians should be aware of the potential for sevelamer-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 3 publications
1
24
0
Order By: Relevance
“…2 Subsequently, Chintamaneni et al described a patient presenting with hematochezia who was found to have a 5 cm ulcer in the sigmoid colon. 3 Biopsy revealed sevelamer crystals entrapped in the ulcer bed. Sevelamer was discontinued without further bleeding, and the authors postulated that sevelamer crystals are directly toxic to the colonic mucosa and may result in ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2 Subsequently, Chintamaneni et al described a patient presenting with hematochezia who was found to have a 5 cm ulcer in the sigmoid colon. 3 Biopsy revealed sevelamer crystals entrapped in the ulcer bed. Sevelamer was discontinued without further bleeding, and the authors postulated that sevelamer crystals are directly toxic to the colonic mucosa and may result in ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The histologic features of sevelamer crystals were first described by Swanson et al in a case series of upper and lower gastrointestinal tract biopsy and resection specimens and were validated by submitting crushed sevelamer tablets for histologic examination. 2 They described the crystals as nonpolarizable with a broad irregularly-spaced fish scale pattern and a two-toned appearance consisting of bright pink accentuations with a rusty yellow background.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Previous case studies showing colonic sevelamer deposition have presented patients with lower gastrointestinal bleeding or diffuse abdominal pain rather than long-standing diarrhea. 2,3 Moreover, sevelamer deposition in the gastrointestinal tract is a relatively novel discovery and its association does not prove causality. Sevelamer first was described as irregularly spaced fish scales that were curved and broad in nature.…”
mentioning
confidence: 99%